How to assess the severity of bronchiolitis epidemics? Application of the Moving Epidemic Method in Nouvelle-Aquitaine, France from 2017 to 2023 - Caroline Couturier; Pascal Vilain; Lindsay S. Cooley; Laurent Filleul (BMC Public Health)
Abstract Background In France, early detection of bronchiolitis epidemics relies on a multi-source surveillance system. However, this system is unable to measure epidemic severity in real time. Such information would enable faster alerts to decision-makers and medical facilities, allowing healthcare provision to be adapted more effectively. This additional information would provide healthcare decision-makers and care structures to be alerted more quickly and to adapt their healthcare provision in a reactive way. In this context, we conducted a study to assess the severity of bronchiolitis epidemics in children under two years of age, from 2017/18 to 2022/23, in Nouvelle-Aquitaine, France. Methods The Moving Epidemic Method (MEM) was used to assess the severity of bronchiolitis epidemics, based on three indicators, obtained from three data sources: (1) virus transmissibility, using data from the SOS Medecins network; (2) impact on the hospital system, assessed via emergency departments (ED) data and (3) gravity, using hospital data. Epidemic thresholds and intensity levels were determined by estimating the parameters of MEM. Results The 2020/21 epidemic was delayed and less severe compared to preceding seasons (2017–2020) across all indicators. In contrast, the 2021/22 and 2022/23 epidemics began early, with prolonged durations. Notably, the 2022/23 epidemic was particularly severe in terms of its impact on the hospital system. Conclusions The intensity of bronchiolitis epidemics in Nouvelle-Aquitaine (2017–2023) was assessed using MEM. This method is a simple, rapid and effective tool for guiding public health interventions.